1993
DOI: 10.1210/endo.133.3.7689960
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide modulates the release of vasopressin from rat hypothalamic explants.

Abstract: The enzyme nitric oxide (NO) synthase is present in the paraventricular nucleus, while nitric oxide has recently been shown to inhibit the stimulated release of corticotrophin-releasing hormone (CRH) in vitro. Thus the possible role of NO in regulating, vasopressin (AVP), which also plays an important role in pituitary-adrenal activity, has been investigated. The effects were studied of the NO donors, L-arginine, syndnonimine-1 (SIN-1) and sodium nitroprusside, on both the basal and stimulated release of AVP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
1
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 0 publications
5
34
1
3
Order By: Relevance
“…The administration of NO donors and NOS antagonists in vivo induce changes in pituitary-gonadal [3], pituitary-adrenal [4, 5] and the neurohypophyseal axes [6], while NO antagonism enhances the responsiveness of the hypothalamo-pituitary-adrenal (HPA) axis to endotoxin administration [4, 5]. This is compatible with other data demonstrating inhibitory modulation by NO of the central regulators of the HPA, corticotropin-releasing hormone (CRH) [7] and vasopressin [8]. Similarly, we have shown that the generation of CO in hypothalamic explants inhibits the secretion of CRH [9] and vasopressin [10].…”
Section: Introductionsupporting
confidence: 75%
“…The administration of NO donors and NOS antagonists in vivo induce changes in pituitary-gonadal [3], pituitary-adrenal [4, 5] and the neurohypophyseal axes [6], while NO antagonism enhances the responsiveness of the hypothalamo-pituitary-adrenal (HPA) axis to endotoxin administration [4, 5]. This is compatible with other data demonstrating inhibitory modulation by NO of the central regulators of the HPA, corticotropin-releasing hormone (CRH) [7] and vasopressin [8]. Similarly, we have shown that the generation of CO in hypothalamic explants inhibits the secretion of CRH [9] and vasopressin [10].…”
Section: Introductionsupporting
confidence: 75%
“…It should be noted that H 2 O 2 may block by itself the enzymatic activity of SOD1 [33], and therefore provoke the intracellular accumulation of O – 2 . Recent evidence also supports that SOD1 downregulation facilitates the reaction of the O – 2 in excess with NO [15], a situation that, in our model, would compromise the normal function of NO as inhibitory factor of neuropeptide release [22, 23, 34]. Consistent with this notion, the present study revealed that a deficit of O – 2 , caused by treating tissues with the SOD1 analogs Mn(III)-porphyrin [27]or TEMPOL [28], could actually reduce both basal and H 2 O 2 -stimulated AVP release.…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, nNOS colocalizes with arginine vasopressin (AVP) and oxytocin in the rat hypothalamus [20, 21], and is also present in the nerve terminals of the neurohypophysis [19]. Furthermore, it has been shown that NO inhibits AVP release from rat-isolated hypothalami [22]and neurohypophysis [23]. Interestingly, this inhibitory effect of NO on neurosecretion is not mediated by cGMP, since the cell permeant cGMP analog 8-bromo-cGMP is unable to affect either basal or isoproterenol-stimulated AVP release from the rat neurohypophysis [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the rat, it is well established that the generation of NO may induce marked neuroendocrine changes, and in particular NO has been shown to inhibit the release of vasopressin both in vitro and in vivo (6,7). Both excitatory and inhibitory effects of NO generation have been shown on CRH release in vitro, but recent in vivo data again suggest a predominant inhibitory modula¬ tion (11).…”
Section: Discussionmentioning
confidence: 99%
“…These hypothalamic nuclei are the major source of corticotrophin-releasing factor (CRH) and vasopressin. Nitric oxide has been shown to inhibit stimulated CRH and vasopressin release in rats (6,7), but data in humans are few. Furthermore, while L-arginine is an established stimulus to growth hor¬ mone (GH) secretion in humans (8), it has not been established previously whether this effect is related to the generation of NO or not.…”
mentioning
confidence: 99%